Improved drought tolerant maize varieties led to improved yields and livelihoods in Nigeria - CGIAR Research Program on Maize (2018)
The Drought_Tolerant_Maize_for Africa (DTMA) project, followed by the Stress_Tolerant_Maize_for_Africa (STMA) project, have delivered valuable results to smallholder_farmers through improved drought and stress tolerant_maize varieties. Over 200 distinct drought_tolerant (DT) maize_hybrids and open_pollinated varieties (OPV) were released throughout the projects_lifetime, of which 54,000 tons of certified DT_maize_seed was produced, benefiting an estimated 5.4 million households_or 43 million people. These impacts continue into the present day_a 2018 ex-post assessment found that adoption of improved_varieties in Nigeria allowed_farmers to increased maize_grain_yield by 574_kg/ha_(32%).